PERANCANGAN SISTEM INFORMASI ADMINISTRASI SEKOLAH -DENGAN MEMANFAATAN DANA KARTU JAKARTA PINTAR (KJP) BERBASIS WEB (STUDI KASUS: SMP DARROSTA JAKARTA) - Hasnan Syah Ahmad; Anita Ratnasari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Darrosta Junior High School Jakarta is one of the private schools in DKI Jakarta that has received assistance from the Smart Jakarta Card (KJP) program where the program provides funds for the needs of school administration fees such as Education Development Donations (SPP). The purpose of this system model is to design a web-based computerized school administration payment information system in utilizing the Jakarta city government program, the Jakarta Smart Card (KJP). This application uses the PHP programming language and in the offline development process Xampp Server is used, which includes the Apache Web Server and MySQL Server as the main requirements for running the system. This information information system provides facilities that can be used by users including input data, search data and student payment reports to assist Administrative Officers (TU) in handling obstacles encountered in conducting transactions, so that the existence of this information system is expected to solve related problems with administration and student needs.